2011
DOI: 10.1371/journal.pone.0027413
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Replication Timing Is Maintained Genome-Wide in Primary Human Myoblasts Independent of D4Z4 Contraction in FSH Muscular Dystrophy

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is linked to contraction of an array of tandem 3.3-kb repeats (D4Z4) at 4q35.2 from 11-100 copies to 1-10 copies. The extent to which D4Z4 contraction at 4q35.2 affects overall 4q35.2 chromatin organization remains unclear. Because DNA replication timing is highly predictive of long-range chromatin interactions, we generated genome-wide replication-timing profiles for FSHD and control myogenic precursor cells. We compared non-immortalized myoblasts from four FSHD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
(92 reference statements)
5
18
0
Order By: Relevance
“…By quantifying the 3D-chromatin organization of the 4q35 locus by 3C and 3D-FISH (Figs. 1C, 2), we report that the organization is similar between conditions when telomeres are long, a finding that is supported by previous replication timing experiments (Pope et al 2011). However, this chromatin organization is sensitive to telomere length in FSHD isogenic clones with short telomeres (Figs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By quantifying the 3D-chromatin organization of the 4q35 locus by 3C and 3D-FISH (Figs. 1C, 2), we report that the organization is similar between conditions when telomeres are long, a finding that is supported by previous replication timing experiments (Pope et al 2011). However, this chromatin organization is sensitive to telomere length in FSHD isogenic clones with short telomeres (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…In FSHD1B, chromosomal looping might be modified by SMCHD1 mutation, which is implicated in chromosomal structural maintenance (Blewitt et al 2008) and/or D4Z4 hypomethylation. However, it remains unclear whether or not FSHD cells have a different 4q35 chromatin organization (Pirozhkova et al 2008;Bodega et al 2009;Pope et al 2011), and no reports have integrated the possible influence of telomere length on the chromatin structure of the 4q35 end (e.g., the last 5 Mb of Chromosome 4).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…1). This extends previous results demonstrating the robust stability of replication profiles between common cell types Ryba et al 2010;Pope et al 2011). The average of all replicates from these four cell lines provides a single B-cell-derived replication-timing profile that will herein be called ''control'' in comparisons with leukemia profiles, with the given caveat that leukemic samples are arrested at various stages in lymphoblast development from immature to more mature pre-B stages (Ferrando et al 2002;Nemazee 2006;Mullighan et al 2007) as indicated by their immunophenotypes where available (Supplemental Table 1).…”
Section: Replication Timing Is Conserved Between Diverse Nonleukemic supporting
confidence: 90%
“…This raised the possibility that they represent misregulation of developmental control over replication timing, as has been described for DNA methylation changes in cancers (Hansen et al 2011;Pujadas and Feinberg 2012). To test this hypothesis, we compared the collection of leukemia fingerprints with profiles of the same genomic regions from nine cell types that we have profiled in the past (Weddington et al 2008;Pope et al 2011;Ryba et al 2011b). More than half of these aligned in register to a developmentally regulated replication domain boundary ( Fig.…”
Section: Replication-timing Fingerprints Align With Developmentally Rmentioning
confidence: 99%
See 1 more Smart Citation